PENGARUH PENERAPAN STRATEGI ACTIVE LEARNING TIPE PLANTED QUESTION TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII MTs MUHAMMADIYAH SILAPING KABUPATEN PASAMAN BARAT - Niswah, Haira; Nursyahra, Nursyahra; Megahati, RRP. (Pendidikan Biologi, 2014)
ABSTRACTÂ Â There are many factors influence the low mark of studentâs Biology achievement. One of them , is the low of student interesting in Biology learning so it become pasive. One way to solue this problem is give an active learning strategi type planted question on student Biology achiment class VIII Â MTs Muhammadiyah Silaping Â Kabupaten West Pasaman. The type of this Â reasearch is Â exprimentalÂ  with Â randomized Â control Â group Â post Â test Â only Â design. Â The population is student from class VIII MTs Muhammadiyah Silaping academik year 2013/2014 which consist of three clas. The sampling technique used here was purposive sampling, which caried VIIICÂ  Â as experimental class and VIIIB as control class. The instrument which was used is test with objective from consist of 30 items. Data analysis was proven by test with criterion tÂ calculate > t table. The result was the everage of Experimental class is 82,37 with branching 6,81 in contrast, control class is gotten 62,58 in average with 12,2 branching. From test, it can be gotten t calcurate (8,84) > t tableÂ  Â (1,67), so it can be concluded Â that learning Biology with active learning strategy type planted question can increase the stundents Biology achievemrnt class VIII MTs Muhammadiyah Silaping.Â